2009
DOI: 10.1128/aem.00557-09
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption ofMycobacterium aviumsubsp.paratuberculosisto Soil Particles

Abstract: Attachment of Mycobacterium avium subsp. paratuberculosis to soil particles could increase their availability to farm animals, as well as influence the transportation of M. avium subsp. paratuberculosis to water sources. To investigate the possibility of such attachment, we passed a known quantity of M. avium subsp. paratuberculosis through chromatography columns packed with clay soil, sandy soil, pure silica, clay-silica mixture, or clay-silica complexes and measured the organisms recovered in the eluent usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…A recent study (4) demonstrated that M. paratuberculosis has negatively charged, hydrophobic walls, and that its transport through positively charged soil particles is slow. A low degree of M. paratuberculosis recovery in loamy (volcanic ash) soil has been explained by a high adsorption rate due to electrostatic and van der Waal's forces and by cell surface hydrophobicity (6). These forces increase at acidic pHs and at a high electrolyte concentrations (24,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study (4) demonstrated that M. paratuberculosis has negatively charged, hydrophobic walls, and that its transport through positively charged soil particles is slow. A low degree of M. paratuberculosis recovery in loamy (volcanic ash) soil has been explained by a high adsorption rate due to electrostatic and van der Waal's forces and by cell surface hydrophobicity (6). These forces increase at acidic pHs and at a high electrolyte concentrations (24,45).…”
Section: Discussionmentioning
confidence: 99%
“…Intact soil core samples that maintained undisturbed soil and plant structures, texture, hydraulic conductivity, and porosity were more accurate in predicting pathogen movement under natural soil conditions (43,49). Two recent studies investigated the passage of M. paratuberculosis through a saturated aquifer and the adsorption of the bacteria to soil particles (4,6). In both studies, factors affecting organism movement and attachment were analyzed in columns containing specific soil types artificially composed in a lysimeter.…”
mentioning
confidence: 99%
“…Furthermore, mycobacteria present in soil samples are easily outgrown by other, faster-growing microorganisms (15). Their strong adherence to soil particles and their viability can also present difficulties in their isolation by culture (4,8). Due to these obstacles, the use of molecular methods for detection and identification of mycobacteria in the environment is favorable.…”
Section: Discussionmentioning
confidence: 99%
“…There are major differences in the cell wall structure of mycobacteria and Gram-negative bacteria. These differences likely affect adsorption to soil particles mediated by van der Waals electrostatic forces or by hydrophobic interactions with the cell surface (19,20). Adsorption to soil would also be affected by soil pH (20).…”
mentioning
confidence: 99%
“…These differences likely affect adsorption to soil particles mediated by van der Waals electrostatic forces or by hydrophobic interactions with the cell surface (19,20). Adsorption to soil would also be affected by soil pH (20). In southern Chile, acidic soils are frequent, with pH values normally ranging from 5.1 to 6.0.…”
mentioning
confidence: 99%